Will Auranofin Become a Golden New Treatment Against COVID-19? - Sonzogni-Desautels, Karine; Ndao, Momar (Frontiers in Immunology, 2021)
Auranofin is an FDA-approved disease-modifying anti-rheumatic drug that has been used for decades for treatment of rheumatoid arthritis. This gold(I) compound has anti-inflammatory properties because it reduces IL-6 expression via inhibition of the NF-kB-IL-6-STAT3 signaling pathway. Also, by inhibiting redox enzymes such as thioredoxin reductase, auranofin increases cellular oxidative stress and promotes apoptosis. Auranofin also possesses antiviral properties. Recently, it was reported that auranofin reduced by 95% SARS-CoV-2 RNA in infected human cells in vitro and decreased SARS-CoV-2-induced cytokine expression, including IL-6. During SARS-CoV-2 infection, a cytokine storm involving IL-6 increases severity of illness and worsens prognosis. Therefore, auranofin could, in our point of view, reduce pathology due to SARS-CoV-2-induced IL-6. COVID-19 is a rapidly-evolving respiratory disease now distributed worldwide. Strikingly high numbers of new COVID-19 cases are reported daily. We have begun a race to vaccinate people, but due to the complex logistics of this effort, the virus will continue to spread before all humans can be immunised, and new variants that may be less well contained by current vaccines are of concern. The COVID-19 pandemic has overwhelmed health care systems and new treatments to reduce mortality are urgently needed. We encourage to further evaluate the potential of auranofin in the treatment of COVID-19 in vitro and in animal models of SARS-CoV-2 infection and, if preliminary data are promising, in clinical trials with COVID-19 patients. In our opinion, auranofin has the potential to become a valuable addition to available therapies in this pandemic.